A revised phylogenetic classification of tribe Phyllantheae (Phyllanthaceae) - Bouman, Roderick W.; Kebler, Paul J.a.; Telford, Ian R.h.; Bruhl, Jeremy J.; Strijk, Joeri S.; Saunders, Richard M.k.; Esser, Hans-Joachim; Falcón-Hidalgo, Banessa; van Welzen, Peter C. (Phytotaxa, 2022)
The majority of tribe Phyllantheae (Phyllanthaceae) is currently placed in the paraphyletic genus Phyllanthus and discussions have persisted on how to resolve this issue. Here, we split Phyllanthus into ten monophyletic genera, which are all reinstatements of former genera, but with changes made to the circumscription and constituent species of each group. The genera Breynia, Glochidion and Synostemon were recently found to be nested within Phyllanthus and discussions ensued whether or not to subsume everything into Phyllanthus s.l. Instead of combining all these genera, we here implement the solution of splitting Phyllanthus into strictly monophyletic genera to ensure that the classification is consistent with the latest phylogenetic results. The new classification is based on a phylogenetic framework combined with differences in habit, branching type, floral, fruit and pollen morphology. With this new division of the genus Phyllanthus, tribe Phyllantheae will consist of the following 18 genera: Breynia, Cathetus, Cicca, Dendrophyllanthus, Emblica, Flueggea, Glochidion, Heterosavia, Kirganelia, Lingelsheimia, Lysiandra, Margaritaria, Moeroris, Nellica, Nymphanthus, Phyllanthus, Plagiocladus and Synostemon. As a result of the reinstated genera, five new names for illegitimate combinations or previous overlooked nomenclatural anomalies and 645 new combinations are proposed. Several keys are provided to distinguish the reinstated genera. Full species lists are given for the reinstated genera treated here except for Breynia, Synostemon and Glochidion.